Evaluasi Kode Klasifikasi untuk Penemuan Kembali Arsip di Balai Diklat Industri Surabaya - Diaz Budi Prasetyo; Tatiana Kristianingsih (STIKes Ibnu Sina Ajibarang, 2025)
Classification codes are an important instrument in the management and storage of archives, serving as a guide to facilitate the retrieval of archives quickly, precisely, and accurately. Classification codes can be letters, numbers, or a combination of both. At the Surabaya Industrial Training Center (BDI), a classification code system has been applied in the filing process. However, as the volume of archives increases every year, there has never been a thorough evaluation to ensure their suitability with the development of existing types of archives and the demands of modern administration. This study aims to evaluate the effectiveness of the classification codes used in BDI Surabaya, especially in supporting the process of rediscovery of archives. The research method used is a descriptive method with data collection techniques through observation, interviews, and field documentation conducted for three months. The results of the study show that the classification code structure at BDI Surabaya is adequate to the tertiary level and facilitates the process of rediscovering old archives. However, the existing system has not accommodated some new types of archives, such as student internship archives and business incubator archives. This classification gap results in delays and inaccuracies in the grouping of archives. In addition, the increase in the average archive volume of 34.7% per year further emphasizes the urgency of updating the classification system to be in line with the development of organizational needs. In conclusion, it is necessary to improve the classification code by adding the PP.03.19 subcode for student internship archives and DL.16 code for business incubator archives. It is also necessary to prepare new SOPs, update the archive list format, and train archivists to improve the effectiveness of archive management.